Ensino Religioso na BNCC e (De)colonialidade do Saber na Escola Pública - Pozzer, Adecir (Numen, 2022)
Although the definition of the Common National Curricular Base (BNCC, 2017) is the object of a series of criticisms due to its supposed alignment with business visions of education, the definition of a curricular guideline for religious education represents a broadening of the horizons of understanding regarding its purpose in the public school. To a certain extent, it solidifies a conception that recognizes and values Brazilian and world religious diversity and, thus, establishes a decolonial process of school knowledge regarding the curricular component that, historically, has been associated with doctrinal assumptions and interests of hegemonic religions. From a critical-understanding perspective and articulating theoretical and methodological assumptions of the Sciences of Religion and Education, our reflection focuses on the openings, challenges and possibilities of intercultural, inter and transdisciplinary dialogues. We believe, therefore, that religious education can contribute to the expansion of anti-hegemonic understandings and foster dialogical perspective in formal formative processes of education in the public school, provided that he himself is not reduced to the reifying role of the human, incapable of problematize prejudiced social representations about the other and recognize respect for different identities, spiritualities and alterities.